2001
DOI: 10.1097/00002281-200103000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Update on work disability in rheumatic diseases

Abstract: Two recent studies suggest the prevalence of rheumatic condition-related work disability is considerably lower than was suggested in previous studies. However, the samples in the recent studies did not include older workers and included persons who gained employment after disease onset. In other recent studies, the rate of work disability among persons employed at disease onset is still high; a fair amount of work disability occurs in the early years of disease. There is no clear evidence yet that treatment im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
67
2
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 25 publications
1
67
2
1
Order By: Relevance
“…In rheumatoid arthritis, several analysts have observed reductions in work disability rates over time (4,25), with some evidence that this may be associated with emerging treatments (26), although it also may be an artifact of methods of analysis or of differences among nations in employment (4). The amount of literature on work disability in persons with SLE is much smaller and, with the exception of 2 of the studies (14,16), the sample sizes of these studies were relatively small and the populations studied were relatively homogeneous.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In rheumatoid arthritis, several analysts have observed reductions in work disability rates over time (4,25), with some evidence that this may be associated with emerging treatments (26), although it also may be an artifact of methods of analysis or of differences among nations in employment (4). The amount of literature on work disability in persons with SLE is much smaller and, with the exception of 2 of the studies (14,16), the sample sizes of these studies were relatively small and the populations studied were relatively homogeneous.…”
Section: Discussionmentioning
confidence: 99%
“…In the rheumatic diseases, work loss accounts for the majority of the economic costs of illness (1). Most of the research on work disability in the rheumatic diseases has focused on rheumatoid arthritis (2)(3)(4)(5)(6)(7)(8). Despite onset at a young age and the potential severity of systemic lupus erythematosus (SLE), there have been relatively few studies of employment among persons with SLE.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have highlighted the devastating emotional and economic consequences of unemployment in patients with rheumatoid arthritis (RA) (1)(2)(3)(4)(5). Most studies have focused on job loss and vocational rehabilitation and have identified predictors of adverse work outcomes, including older age, less education, less social support, not wanting to work, multiple social roles, and more depressive symptoms (3)(4)(5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings have also been described in patients with RA (13,27), and highlight that early detection of patients at risk of work disability is important. Evidence is emerging that interventions aimed at preventing work disability may be more effective than job accommodations or changing jobs (28,29). In particular, it may be difficult to get people back to work once they have left the job market (28).…”
mentioning
confidence: 99%
“…Evidence is emerging that interventions aimed at preventing work disability may be more effective than job accommodations or changing jobs (28,29). In particular, it may be difficult to get people back to work once they have left the job market (28). Methods anticipated to prevent work disability should be multifaceted.…”
mentioning
confidence: 99%